Efektifitas Pembelajaran Pendidikan Multi Agama pada Perubahan Perilaku Pergaulan Bebas Siswa Kelas XI SMKN 1 Negara Kabupaten Jembrana Provinsi Bali - Prasetyo R., Dwi; Nadlif, Aiunun (Indonesian Journal Publisher, 2020)
This study aims to describe: (1) How are students interacting at SMKN 1 State, Jembrana Regency, Bali Province (2) How is the negative impact of promiscuity in Smkn 1 State School, Jembrana Regency, Bali Province (3) How is promiscuity in the perspective of existing religious education in Indonesia. This research is a descriptive qualitative research, data collection techniques with the method of observation (observation), interviews and documentation. Data analysis using data analysis techniques, namely data reduction, data presentation, conclusion and verification. Based on the research results show that: (1) The impact of promiscuity on students in Smkn 1 Negara such as, decreased school achievement (study achievement), dropping out of school, pregnancy out of wedlock. (2) If it is connected with the 2013 curriculum material for Islamic religious education, it is found that it is already present in teaching, namely self-control behavior (mujahaddah-nafs) described in QS. al-Anfal verse 72, and there are also teachings about promiscuity which include understanding the meaning, negative effects and dangers of major sins such as drunkenness, taking drugs, adultery and others and it is also explained that parents and playmates must be figures who can set a good example. As for promiscuity and its negative impact in terms of Islamic education, it is the procedure for association between humans and fellow human beings, especially with the opposite sex which leads to the implementation of sex outside of marriage which has destructive consequences and deviant behavior that leads to promiscuity which is contrary to values. values contained in Islamic education.